To study the prevalence of latent tuberculosis infection among medical students - Dinkar, Prateek Kumar; Kumar, Santosh; Kumar, Sukriti; Verma, Sanjeev Kumar; Kumar, Sandeep; Kamal, Ankita; Chaudhary, Esha (Indian Journal of Community Health, 2022)
Background: Risk of developing latent tuberculosis infection increases in medical students with their higher exposure to TB care facilities. Objective: To study the prevalence of latent TB infection among students attending professional degrees MBBS, BDS, MD, MS, MDS at King George’s Medical University, India. Methods: This study was carried out with Tuberculin skin testing among students and active TB cases were excluded. A standard dose of 0.1?mL of purified protein derivative was slowly injected intra dermally into non-dominant forearm. After 48-72 hours, the reaction was estimated by measuring the transverse diameter of the induration. Results: Total 561 students had given consent to get enrolled. Prevalence of latent tuberculosis infection was significant with period of clinical exposure (p-value < 0.05), average size of induration (p-value < 0.001), and history of prior Tuberculin Skin Test (p-value < 0.001). However it was not significant with the age (p-value > 0.05), gender (p-value > 0.05), and history of contact with active cases of TB (p-value > 0.05). Conclusion: The prevalence of latent tuberculosis infection is higher in post graduate students followed by interns and final year students due to more exposure to patients in wards and clinics at King George’s Medical University, India.